PENGEMBANGAN KONSTRUKSI KAPAL PADA KAPAL PINISI DENGAN MENGGUNAKAN LAMBUNG LAMINASI - Nurul Hijrah Bahar; Cici Faradilah (Riset Sains dan Teknologi Kelautan, 2024)
The development of shipping technology continues with the discovery of new construction methods to achieve fast and cost-effective results. The development of shipping technology is starting to show a better direction and shipping as a means of transportation has become a very promising business for the shipping industry in Indonesia. This is different from the construction of civil ships, where the legal process is still traditional and takes a long time, especially for private ships. It is very important to pay attention to the factors that influence the condition of the ship. Factors related to ship performance and productivity must of course be taken into account, especially when calculating ship cargo. Because increasing the load will reduce the maximum load that the ship can carry and automatically affect the stability of the ship, etc. Under these conditions, it is necessary to calculate the performance of the ship's steel that will be used later so that the collection is in accordance with the ship owner's expectations. The development of working methods is considered negative due to differences in current conditions, especially in the manufacturing sector, especially in the quality of technology and human resources. Therefore, one of the methods used is the lamination technology method, which combines one or more types of materials into one